Amplification-free electrochemiluminescence biosensors based on peptide-templated gold nanocluster and CRISPR-Cas12a for Mycobacterium tuberculosis IS6110 detection - Lingjun Cheng; Qingmei Yang; Yuanyuan Yang; Yufeng Wang; Qingfei He; Zhiyan Zou; Canping Su; Jiaming Chen; Yinhuan Liu; Guolin Hong (Analytica Chimica Acta, 2026)

Contrasting Resource-Use Strategies Under Tropical Stress: Linking Leaf Functional Traits to Fruit Biomass and Oil Yield in Camellia Oleifera - Wenjun Hong; Jindian Yang; Shufen He; Jiaming Song; Weiyu Chen; Zhitong Mai; Feifei Chen; Ling Lin; Chuanteng Huang (Tropical Plant Biology, 2026)

Hybrid framework combining machine learning with mechanism models for enhanced forecasting of biomass gasification products - Jiaming Song; Zongqi Chen; Haining Tang; Hong Ding; Shiliang Wu; Zhou Liu; Feng Gong (Bioresource Technology, 2026)

Low-cost, scalable fabrication of antibacterial asymmetric hydrogels inspired by mangrove systems for superior oil-water separation and salt-tolerant evaporation - Qidong Zha; Zuozhu Yin; Yingping Yang; Guoyan Yang; Jiaming Ni; Jilin Xu; Zhen Hong; Chan Xie; Yidan Luo; Mingshan Xue (Water Research, 2026)

Heterogeneous distribution of salinity and nitrogen in the root-zone influence nitrogen harvest index and natural 15N abundance of tomato - Jinjing Liu; Zhenchang Wang; Yuexiong Wang; Yaosheng Wang; Yousef Alhaj Hamoud; Cheng Hong; Hiba Shaghaleh; Rangjian Qiu; Jiaming You; Minghao Tian; Kexin Chen; Xiaoman Qiang; et al. (Plant Science, 2026)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

Prevalence of common upper gastrointestinal diseases in Chinese adults aged 18–64 years - Hong Yang; Mei Zhang; Hui Li; Zhengjing Huang; Yuanyuan Sun; Wenbo Li; Chun Li; Xuzhen Qin; Yanhong Wang; Xiao Zhang; Zhenping Zhao; Limin Wang; et al. (Science Bulletin, 2024)

Spatial Patterns and Drivers of Intelligent Manufacturing from a ‘Global-local’ Perspective: A Study of China’s Industrial Robotics - Fengjiao Li; Hong Zhang; Lili Jiang; Jiaming Liu (Chinese Geographical Science, 2024)

Sensitive and quick electrochemiluminescence biosensor for the detection of reactive oxygen species in seminal plasma based on the valence regulation of gold nanoclusters - Lingjun Cheng; Yuanyuan Yang; Shaobin Lin; Canping Su; Mingming You; Yating Liu; Qingfei He; Jiaming Chen; Zhenyu Lin; Guolin Hong (Analytica Chimica Acta, 2024)

Thermal inactivation kinetics of Listeria monocytogenes in milk under isothermal and dynamic conditions - Xiang Wang; Jiaming Zheng; Linyin Luo; Yi Hong; Xiaofeng Li; Yuqi Zhu; Yufan Wu; Li Bai (Food Research International, 2024)

miR-24-3p Regulates Epithelial–Mesenchymal Transition and the Malignant Phenotype of Pancreatic Adenocarcinoma by Regulating ASF1B Expression - Wentao Huang; Tiansheng Lin; Long Huang; Junyi Wu; Jiaming Hong; Funan Qiu; Yifeng Tian; Yaodong Wang (Biochemical Genetics, 2023)
Anti-silencing function protein 1 homolog B (ASF1B) has been implicated in the occurrence and development of cancers. The present work explored the functional role and the expression regulation of ASF1B in pancreatic ductal adenocarcinoma (PDAC). Based on the real-time quantitative PCR (qRT-PCR) and immunohistochemistry (IHC), ASF1B was significantly upregulated in PDAC tissues. High expression of ASF1B was associated with a poor overall survival (OS) and recurrence-free survival (DFS) in the PDAC patients. ASF1B also showed a relatively higher expression in PDAC cells (AsPC-1, PANC-1) when compared with human pancreatic ductal epithelial cells (HPDFe-6). CCK8 and clone formation assay demonstrated that silencing ASF1B impaired the proliferation in PANC-1 and AsPC-1 cells, and Annexin V-PI staining showed an increased level of apoptosis upon ASF1B silencing. ASF1B silencing also suppressed the migration and invasion in PDAC cells, as revealed by Transwell assays. We further showed that miR-24-3p was downregulated in PDAC tissues and cells, which functionally interacted with ASF1B by dual-luciferase reporter assay. miR-24-3p negatively regulated ASF1B expression to modulate the malignant phenotype of PDAC cells. ASF1B shows high expression in PDAC, which promotes the malignancy and EMT process of PDAC cells. miR-24-3p is a negative regulator of ASF1B and is downregulated in PDAC cells. Our data suggest that targeting ASF1B/miR-24-3p axis may serve as an intervention strategy for the management of PDAC.

Role of rgsA in Oxidative Stress Resistance in Pseudomonas aeruginosa - Shuyi Hou; Jiaqin Zhang; Xiaobo Ma; Qiang Hong; Lili Fang; Gangsen Zheng; Jiaming Huang; Yingchun Gao; Qiaoli Xu; Xinguo Zhuang; Xiuyu Song (Current Microbiology, 2021)

A Highly Sensitive Solid Substrate Room Temperature Phosphorimetry for Carbaryl Detection Based on its Activating Effect on NaIO4 Oxidizing Fluorescein - Jiaming Liu; Qitong Huang; Zhen-bo Liu; Xiaofeng Lin; Li-Hong Zhang; Chang-Qing Lin; Zhi-Yong Zheng (Journal of Fluorescence, 2014)

Contribution of the IBD5 locus to inflammatory bowel disease: a meta-analysis - Jian Wang; Xi Wang; Hong Yang; Dong Wu; Li Wang; Jiaming Qian (Human Genetics, 2011)